Insulin-like growth factor 1 promotes the proliferation and committed differentiation of human dental pulp stem cells through MAPK pathways. (December 2016) - Lv, Taohong; Wu, Yongzheng; Mu, Chao; Liu, Genxia; Yan, Ming; Xu, Xiangqin; Wu, Huayin; Du, Jinyin; Yu, Jinhua; Mu, Jinquan
Highlights: IGF-1 can up-regulate the ALP activity and mineralization capacity of hDPSCs. MAPK signaling pathway is activated during the differentiation of hDPSCs. IGF-1 promotes the proliferation and osteogenic/odontogenic differentiation of hDPSCs. Abstract: Objectives: Insulin-like growth factor 1 (IGF-1) is a broad-spectrum growth-promoting factor that plays a key role in natural tooth development. Human dental pulp stem cells (hDPSCs) are multipotent and can influence the reparative regeneration of dental pulp and dentin. This study was designed to evaluate the effects of IGF-1 on the proliferation and differentiation of human dental pulp stem cells. Methods: HDPSCs were isolated and purified from human dental pulps. The proliferation and osteo/odontogenic differentiation of hDPSCs treated with 100 ng/ml exogenous IGF-1 were subsequently investigated. Results: MTT assays revealed that IGF-1 enhanced the proliferation of hDPSCs. ALP activity in IGF-1-treated group was obviously enhanced compared to the control group from days 3 to 9. Alizarin red staining revealed that the IGF-1-treated cells contained a greater number of mineralization nodules and had higher calcium concentrations. Moreover, western blot and qRT-PCR analyses demonstrated that the expression levels of several osteogenic genes (e.g., RUNX2, OSX, and OCN) and an odontoblast-specific marker (DSPP) were significantly up-regulated in IGF-1-treated hDPSCs as compared with untreated cells (P < 0.01). Interestingly, the expression of phospho-ERK and phospho-p38 were also up-regulated, indicating that the MAPK signaling pathway is activated during the differentiation of hDPSCs. Conclusions: IGF-1 can promote the proliferation and osteo/odontogenic differentiation of hDPSCs by activating MAPK pathways.